Predictive Role of C-Reactive Protein Ferritin D-Dimer and Interleukin-6 in Determining COVID-19 Severity and Outcomes - AHMAD, TANVEER; NOOR, AHMAD; ULLAH, IKRAM; MALIK, SAUD; ALI, WAJID; SALEEM, IFTIKHAR (Pakistan Journal of Medical & Health Sciences, 2026)
Background: The unpredictable clinical course of COVID-19 has led to an urgent need for early prognostic biomarkers. Among the most studied markers are C‑reactive protein (CRP), ferritin, D‑dimer, and interleukin‑6 (IL‑6), which may reflect underlying inflammation, coagulopathy, and cytokine response. Aim: To evaluate the predictive role of CRP, ferritin, D‑dimer, and IL‑6 levels in determining the severity and clinical outcomes of COVID‑19 among hospitalized patients at Lady Reading Hospital, Peshawar. Methodology: A descriptive cross‑sectional study was conducted at Lady Reading Hospital, Peshawar, from August to December 2024. A total of 200 RT‑PCR‑confirmed COVID‑19 patients were enrolled. Serum CRP, ferritin, D‑dimer, and IL‑6 levels were measured on admission. Patients were classified into mild, moderate, and severe categories based on WHO guidelines. Outcomes such as ICU admission, need for mechanical ventilation, and mortality were recorded. Results: Elevated levels of CRP, D‑dimer, and IL‑6 were significantly associated with severe disease (p<0.001). Ferritin levels were also higher in severe cases but showed moderate predictive value (p=0.042). IL‑6 and D‑dimer had the strongest correlation with ICU admission and mortality. Conclusion: CRP, D‑dimer, and IL‑6 are valuable biomarkers for early prediction of disease severity and poor outcomes in COVID‑19. Routine measurement of these markers at Lady Reading Hospital may guide clinical decision‑making and resource allocation.